Director's Report of Research in Kansas, 2018 and 2019 - J. E. Minton (Kansas Agricultural Experiment Station Research Reports, 2020)
The Director’s Report of Research in Kansas includes a list of journal articles, station publications, and other published manuscripts from scientists in our departments, research-extension centers, and associated programs.
Keywords: Agricultural research